Mental Health Burden in Higher Education: Exploring the Impact of Bullying, Social Support, and Happiness on Psychological Distress and Suicidal Ideation in Pakistani Students - Siyal, Fahad Jibran; Mahar, Muiz-U-Din; Memon, Khushboo Sarwar; Sheikh, Adeel Ahmed; Sheikh, Iqra Nawaz; Das, Dial; Chahwan, Adnan Ali; Jiskani, Shahzad Ali; Dodani, Amar; Tunio, Fatima; Lund, Nadeem; Shaikh, Bakhtawer; et al. (Indus Journal of Bioscience Research, 2025)
Background: University students face increasing psychological pressure due to academic demands, social changes, and limited mental health support – particularly in low-resource settings like Pakistan. Mental health disorders, suicidal ideation, and bullying are interlinked concerns with significant implications for student well-being, yet are underexplored collectively in the Pakistani context. Objective: To assess the prevalence of depression, anxiety, stress, and suicidal ideation among university students, and to evaluate the association of these outcomes with bullying, subjective happiness, and perceived social support. Methodology: A cross-sectional study was conducted at SMMBMU, Larkana from October to December 2024. A stratified random sample of 372 valid responses analyzed. Data were collected using a self-administered online questionnaire including DASS, SHS, and the F-SozU Social Support Scale. Statistical analyses were performed using SPSS v.24.0. A p-value of